Peran Sutradara dalam Pembuatan Karya Video Feature “Thrift or Threat: Health Issues in the Thrifting Phenomenon” Dengan Pendekatan Storytelling - Muhammad Arif Rahman; Dian Wardiana Sjuchro; Agus Setiaman (BADAN PENERBIT STIEPARI PRESS, 2025)
Thrifting, while a popular affordable fashion alternative, raises concerns about safety and health risks for enthusiasts. The feature video